Impact of the CAP reform on small-scale grassland regions - Norbert Roeder; Jochen Kantelhardt; Martin Kapfer (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2006)
This paper presents a regional land-use model that conceives farms as independent agents aiming at maximum individual utility. Farm agents optimize their utility with the help of a linear-programming algorithm that takes into account natural, economic and personal restrictions. Interactions between farms take place on the land market, which is modelled as an equilibrium market. The model is applied in three typical grassland regions in southern Bavaria. The results indicate that the CAP reform of 2003 has various significant consequences for grassland use. In particular, the decreasing profitability of dairy farming will lead to low-intensity forms of grassland use, including mulching. In general, land rents will increase due to the effects of decoupling.
Keywords: 330; EU-Agrarpolitik; Agrarreform; Wirkungsanalyse; Bodenmarkt; Tierhaltung; Simulation; Mathematische Optimierung; Bayern; Agentenbasierte Modellierung